Epidemiology of complex bone and joint infections in France using a national registry: The CRIOAc network. Issue 2 (February 2021) - Lemaignen, Adrien; Bernard, Louis; Marmor, Simon; Ferry, Tristan; Grammatico-Guillon, Leslie; Astagneau, Pascal; ,
Highlights: Epidemiology of bone and joint infections in a national cohort of 27, 483 patients. Multidisciplinary decisions for the management of complex infections. Prevalence of prosthetic joint infections, representing half of national cases. Description of types, sites, microbiology and medico-surgical management. Abstract: Objectives: In France, a network of reference centers for bone and joint infections (BJI) was created in 2008, focused on the management of complex BJI (previous failure, difficult-to-treat microorganisms, heavy comorbidities or surgical procedures). A national registry was implemented from 2012, collecting decisions advised in periodic multidisciplinary meetings. We present here an epidemiological overview. Methods: All consecutive adult patients presented from 2014 to 2019 in 23/30 reference centers were included in this cohort. Characteristics of patients, BJI, and medico-surgical management advice were described. Results: 27, 483 individual patients were included, corresponding to 28, 365 distinct infectious episodes, which 17, 328 were complex. Median age was 65 years, with 62% of men, 1/3 patients presented more than 2 comorbidities. Prosthetic joint infections (PJI) represented 42% of all BJIs (11, 812 episodes). Staphylococcus aureus, coagulase-negative staphylococci and polymicrobial PJI represented 26%, 25% and 16% respectively. DAIR (debridement, antibiotics and implant retention) was proposed for 3, 157 (27%), whereas one-stage and two-stage revision for 3, 683 (31%) and 1, 764 (15%). An antibiotic treatment was advised in 10, 493 episodes (87%), with combination therapy in 88%. Conclusion: This national network allows an optimized management of complex BJIs. Its cohort is a unique opportunity to draw up a detailed epidemiological picture and to follow the trends of these infrequent infections.